Eye-hand and eye-foot visual reaction times of young soccer players - Montes-Mico, R.; Bueno, I.; Candel, J.; Pons, A. M. (Optometry - Journal of the American Optometric Association, 2000)
PURPOSE: The aim of this study was to investigate the eye-hand and eye-foot visual reaction time among young soccer players and to compare those with non-soccer players in order to evaluate possible differences. METHODS: A vision screening of 53 young male soccer players belonging to the Valencia Soccer Club was done. Soccer players were divided in three categories, with mean ages of 8.2 +/- 0.5 years (range, 8- to 9-year olds), 10.6 +/- 0.2 years (range, 10- to 11-year-olds), and 12.7 +/- 0.3 years (range, 12- to 13-year-olds). An age-matched sample of 60 young male non-soccer players served as a control population. Mean ages in this population were 8.3 +/- 0.6 years, 10.5 +/- 0.4 years, and 12.6 +/- 0.2 years for each category, respectively. Eye-hand and eye-foot visual reaction times were determined in players and non-players by means of a computer-controlled stimuli device. RESULTS: We obtained a mean and standard deviation value (in seconds) of eye-hand reaction time in soccer players of 0.301 +/- 0.037, 0.256 +/- 0.040, and 0.207 +/- 0.031, respectively, for each category, and for non-soccer players of 0.382 +/- 0.061, 0.320 +/- 0.063, and 0.282 +/- 0.043, respectively. The values for eye-foot reaction time in players were: 0.412 +/- 0.062, 0.406 +/- 0.046, and 0.387 +/- 0.034, respectively, for each category, and for nonplayers of 0.496 +/- 0.081, 0.460 +/- 0.026, and 0.446 +/- 0.054, respectively. There are statistically significant differences between eye-hand and eye-foot reaction times between players and nonplayers (p < 0.05). There was no correlation between visual reaction times and age (p > 0.05). CONCLUSIONS: Eye-hand and eye-foot visual reaction times were found to be different between the two populations evaluated. The results show differences between soccer and non-soccer players, with the soccer players demonstrating faster reaction times.